PROMOTION IMPLEMENTATION THROUGH SOCIAL MEDIA IN THE TOURISM SERVICE OF RIAU PROVINCE - Rizki Simatupang; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Riau province became the top five in internet penetrase in Sumatra. That states that Riau Province is well worth doing all activities in the digital world. Social Media promotion itself is certainly able to increase the number of tourist visits to Riau Province, under the pretext of the internet spread inside without knowing the time limit, place, and also status. This is a serious step that will be known about the smooth running of social media itself. This research aims to find out what promotions and media are chosen in the promotion. Based on the method used in this study is a qualitative descriptive method to analyze the problems collected by the authors through interviews, observations, and documentation with the marketing authorities of Riau Provincial Tourism Office. Based on the analysis of promotional data through social media is very influential in the smooth promotion of Twitter, Facebook, and Instagram itself. Keywords: Implementation of Social Media, Twitter, Facebook, Instagram